TRADITIONAL FISHING ACTIVITIES OF KARAKALPAKS IN FERGANA VALLEY (Field Ethnographic Data Analysis) - Atakhanov Rafikjon Sotvoldievich (Journals Park Publishing, 2022)
In this article, on the basis of scientific literature and field ethnographic studies, based on the peculiarities of their lifestyle and geographical mixing, the traditional economic fishing activity of the Karakalpaks of the Fergana Valley is analyzed.
Keywords: Ferghana Valley; Karakalpaks; Syrdarya